2022
DOI: 10.4012/dmj.2021-062
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of S-PRG filler eluate on MMP-1 and MMP-3 secretion by human gingival fibroblasts

Abstract: The aim of this study was to investigate the effects of surface reaction-type pre-reacted glass-ionomer (S-PRG) filler eluate on Matrix metalloproteinase (MMP)-1 and MMP-3 secretion by human gingival fibroblasts (HGF). The S-PRG filler eluate contains 6 ions (F, Na, Al, B, Sr and Si) released from the S-PRG filler. The S-PRG filler eluate stimulation induced a slight secretion of MMP-1 and MMP-3 by HGF. It also enhanced the phosphorylation of p38 and ERK. The increase in MMP-1 and MMP-3 secretion by the inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the activation of MAP kinase via NOD-2 was demonstrated in murine macrophages, in which p38, ERK 1/2, and JNK were phosphorylated after a stimulation with MDP 17) . We previously demonstrated that ERK 1/2 was involved in MMP-1 production by human gingival fibroblasts stimulated with S-PRG filler eluates 16) . Therefore, in the present study, we investigated changes in ERK1/2 phosphorylation upon a co-stimulation with MDP and S-PRG filler eluate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the activation of MAP kinase via NOD-2 was demonstrated in murine macrophages, in which p38, ERK 1/2, and JNK were phosphorylated after a stimulation with MDP 17) . We previously demonstrated that ERK 1/2 was involved in MMP-1 production by human gingival fibroblasts stimulated with S-PRG filler eluates 16) . Therefore, in the present study, we investigated changes in ERK1/2 phosphorylation upon a co-stimulation with MDP and S-PRG filler eluate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, S-PRG filler eluate appears to endow pulp capping with several beneficial properties, leading to reparative dentin. We previously demonstrated that S-PRG filler eluate enhanced the production of MMPs by human gingival fibroblast cells 16) . MMP-1 levels were increased by MDP, resulting in the development of inflammation, such as pulpitis 7) .…”
Section: Effects Of a Co-stimulation With S-prg Filler Eluate And Mur...mentioning
confidence: 97%
See 1 more Smart Citation